2016
DOI: 10.1039/c6sm01796g
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic BODIPY derivatives: the solvophobic effect on their photophysical properties and bioimaging in living cells

Abstract: Three novel amphiphilic BODIPY derivatives were prepared and their photophysical properties in THF/water mixtures with varying fractions of water were investigated. BDP-1 could self-assemble into different vesicle architectures in aqueous solution, while BDP-2 and BDP-3 with more hydrophilic abilities formed spherical and worm-like micelles. The BODIPY derivatives could be absorbed by HeLa cells and showed no apparent toxicity during the course of the test. In particular, unlike traditional amines or morpholin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 39 publications
1
24
0
Order By: Relevance
“…Laser scanning fluorescence microscopy (LSFM) was used to investigate the cell bioimaging potential of SDP. Based on our previous experience that the fluorescent intensities might be dependent on the incubation time due to the large aggregate size, we collected the images at different time intervals and found that the SDP showed red emission, which was consistent with our previous observation. In addition, the intensities were correlated with the incubation time as well ( Figure ).…”
Section: Methodssupporting
confidence: 90%
“…Laser scanning fluorescence microscopy (LSFM) was used to investigate the cell bioimaging potential of SDP. Based on our previous experience that the fluorescent intensities might be dependent on the incubation time due to the large aggregate size, we collected the images at different time intervals and found that the SDP showed red emission, which was consistent with our previous observation. In addition, the intensities were correlated with the incubation time as well ( Figure ).…”
Section: Methodssupporting
confidence: 90%
“…Formyl‐modified OEG dendrons 1 followed a classic synthetic pathway to BODIPY derivatives to afford target molecule 2 . Then, compound 2 underwent a Knoevenagel reaction with 1‐pyrenecarboxaldehyde to generate the final BBDP product . PBI and MV were obtained according to the literature .…”
Section: Resultsmentioning
confidence: 77%
“…BBDP: Compound 2 (100 mg, 0.11 mmol), 1‐pyrenecarboxaldehyde (100 mg, 0.44 mmol), and p ‐toluenesulfonic acid ( p ‐TsOH, 10 mg) were dissolved in a mixture of toluene (25 mL) and piperidine (1 mL). The mixture was stirred at 120 °C for 2 h under the protection of N 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the luminescent POPs with tunable surface morphologies have rarely been referred. We have been interested in fluorescent amphiphilic 4,4‐difluoro‐4‐bora‐3a,4a‐diaza‐s‐indacene (BDP) derivatives since 2014 . Very recently, a novel about dimeric BDP molecules based POPs could be realized by using FeCl 3 at room temperature was reported .…”
Section: Introductionmentioning
confidence: 99%